The ecophysiology of selected coastal dune pioneer plants of the Eastern Cape - Ripley, Bradford Sherman (Rhodes University, Faculty of Science, Botany Department, 2002)
Understanding the mechanisms and adaptations that allow only certain species to thrive in the potentially stressful foredune environment requires a knowledge of the basic ecophysiology of foredune species. Ecophysiological measurements were conducted on the foredune pioneer species Arctotheca populifolia (Berg.) Norl., Ipomoea pes-caprae(L.) R. Br. and Scaevola plumieri (L.) Vahl. and showed significant differences among species with respect to the physiology associated with biomass production, water and nutrient relations. Differences related to CO₂ assimilation included differences in photosynthetic and respiratory rates, susceptibility to light stress and leaf and stem non-structural carbohydrate concentrations. These resulted in differences in primary production rates of shoots. Mechanisms leading to the differences in CO₂ assimilation among species included differences in stomatal behaviour, carboxylation efficiencies, efficiencies of utilisation of incident photosynthetic photon flux density (PPFD) and rates of ribulose-1,6-bisphosphate (RuBP) regeneration. Correlated with differences in photosynthetic capacity were differences in chlorophyll contents but not differences in leaf nitrogen content. Differences in interspecific stomatal behaviour resulted in significantly different transpiration rates which in combination with differences in assimilation rates resulted in differences in water-use efficiency. The absolute amounts of water transpired, although significantly different among species, were moderate to high in comparison with species from other ecosystems and were typical of mesophytes. Transpiration rates in combination with plant hydraulic conductances and soil water availability resulted in leaf water potentials that were not very negative and none of the investigated species showed evidence of osmotic adjustment. The volume of water transpired by each of the species per unit land surface area was estimated from the relationship between abiotic factors and plant water loss. These relationships varied among species and had varying degrees of predictability as a result of differences in stomatal behaviour between the three species. The water requirements of A. populifolia and S. plumieri were adequately met by the water supplied by rainfall and the water stored in the dune sands. It was therefore not necessary to invoke the utilisation of ground water or the process of internal dew formation to supply sufficient water to meet the requirements. However, I. pes-caprae despite its lower transpiration rates and due to its higher biomass, lost greater volumes of water per unit dune surface area than either A. populifolia or S. plumieri. This resulted in periods of potential water limitation for I. pes-caprae. Incident light was the most important determinant of leaf photosynthetic CO₂ assimilation and transpiration, particularly as a linear relationship between incident PPFD and atmospheric vapour pressure deficit (VPD) could be demonstrated. Whole plant photosynthetic production by S. plumieri was shown to be light limited as a result of mutual shading despite high incident and reflected PPFD occurring in the foredune environment. The leaf hair-layer of A. populifolia was shown to be important in reducing transmitted UV and hence reducing photoinhibition but it also caused reduced transpiration rates because of the thicker boundary layer and thus increased leaf temperatures. The nutrient content of above-ground plant parts of the investigated species were typical of higher plants despite the low nutrient content measured for the dune soils. With the possible exception of nitrogen the nutrient demand created by above-ground production was adequately met by the supply of nutrients either from sand-water or from aquifer-water transpired by the plants. Differences in the volumes of water transpired, and hence the quantity of nutrients potentially taken up via the transpiration stream, resulted in interspecific differences in above-ground plant macronutrient content. The reallocation patterns of nutrients differed both between the various nutrients measured and interspecifically. Standing biomass and the density of plants per unit land area was low in comparison to that of other ecosystems and was different among investigated species. This may be important in maintaining the adequate supply of resources (water, nutrients and light). As a result of the interspecific differences in biomass when production was expressed per unit land surface area the resultant productivity was not dissimilar among species. Productivity was high when comparisons were made with species from other ecosystems. No single resource (water, nutrients or light) could be identified as the controlling factor in the foredune environment and a combination of both resource stress and environmental disturbance are likely to be involved. Physiology, production, growth and growth characteristics conveyed certain adaptive advantages to these species in respect to both resource stress and environmental disturbance. Interspecific differences in these adaptations can be used to offer explanations for the observed microhabitat preferences of the three investigated species. Furthermore features common to all three species offer some explanations as to why these species and not others are able to inhabit the foredunes.
Keywords: Sand dune plants -- South Africa -- Eastern Cape; Sand dune ecology -- South Africa -- Eastern Cape; Sand dune plants -- Ecophysiology